Restaurer les milieux et prévenir les inondations grâce au génie végétal - Rey, Freddy (éditions Quae, 2018)
Public policies in France and in Europe obligate decision makers to consider an integrated management of habitats and territories that combines several benefits. This book provides innovative vegetation engineering solutions for reconciling habitat restoration with flood prevention.